Increase of the Biogas Output during Fermentation of Manure of Cattle with Winemaking Waste in Biogas Plants - Polishchuk V.M.; Shvorov S.A.; Krusir G.V.; Davidenko T.S. (Problems of the Regional Energetics, 2020)
The aim of the work is to increase biogas output and generation of electricity in biogas plants due to the joint fermentation of cattle manure with winemaking waste. To achieve this goal, the following tasks have been solved: the biogas yield from cattle manure with winemaking waste was determined during periodic loading of the digester; based on the obtained experimental data, a mathematical model was calibrated to estimate the biogas yield during fermentation of cattle manure with the addition of winemaking waste. Because of the studies, it had been found that when manure was fermented with part of the water replaced in the substrate 2% of the winemaking waste, the fermentation dynamics in the substrate are similar to the fermentation of pure cattle manure. Biogas obtained by fermentation of manure with the addition of 2%, 6.5% and 13% of wastewater from wine production instead of water in the first day of fermentation either did not burn at all or burned poorly. The addition of winemaking waste to a substrate based on manure in an amount of 13% allows increasing the maximum biogas yield by a third to 1,372 l/(hrkg dry organic matter). The significance of the research results lies in the fact that the use of winemaking waste as a substrate will allow a third increase in biogas output and power generation, and a reduction in the payback period of a 4,4 MW biogas plant using the green tariff to 6,5 years.